Tutuku: Telling the stories of the Māori Showband world through digital innovation - Kewene-Doig, Louise (Te Kaharoa, 2021)
In this article I will discuss the development and creation of the Tutuku digital archive. Tutuku is the name of the digital archive I have created as my nominated creative component for my PhD. Tutuku is coupled with my thesis “He Kohinga Kōrero: A selected group of Māori musicians and performers’ experiences of the 1960s through the Māori Showband movement”. Tutuku contains people’s narratives and experiences, which in turn each have their own mauri or life principle (objectspace, 2020). The narratives could also be described as mana taonga. Mana taonga is a specific Māori curatorial concept that taonga have their own status and power which must be managed and cared for in a culturally appropriate way (Mccarthy, Dorfman, Hakiwai, and Āwhina, 2013, 7). The concept of mana taonga creates the space for indigenous voices to be self-determining in history retelling. Tutuku creates pathways for expanding knowledge on many other subjects. Tutuku is available as an IOS App and web application located at Www.tutuku.co.nz. The second version will be available exclusively for Android devices in the Future. Tutuku will continue on into the future, to be a safe digital space for the sharing of indigenous experiences, culture and histories.